Overconfident CEOs and Corporate Tax Avoidance: Array - Ilaboya, Ofuan James; Aronmwan, Edosa (The Journal of Accounting and Management, 2021)
The upper echelon theory predicts that the personalities, attributes, and skills of the managerial cadre should have an influencing role in the culture, practices, and outcomes within an organisation. In light of this prediction, this paper examines how overconfident CEO may affect tax avoidance practices. Tax avoidance was captured using the measure developed by Henry and Sansing while CEO overconfidence was captured using firm-level investment. Based on the analyses of 660 firm-year observations of non-financial firm, the study found that overconfident CEOs are associated with corporate tax avoidance. This finding is consistent with the upper echelon theory and helps tax authorities and officers understand the roles that an overconfident CEO may play towards tax avoidance. It is recommended that tax regulators can employ the technique of CEO profiling as a preliminary selection tool that can be used pick companies for tax audit and investigations.